ECOWAS and the Restoration of Democracy in the Gambia. Issue 1 (April 2017) - Hartmann, Christof
Following the disputed December 2016 presidential elections in The Gambia, ECOWAS managed to "restore democracy" in the country by using the threat of force, but without any use of direct physical violence. Both the African Union and the United Nations Security Council backed ECOWAS, which also gave ECOWAS legitimacy, for what was essentially ECOWAS's policy, and indeed an African solution to African problems. Only when the scenario of military invasion became credible did the Gambian regime accept the defeat. Four main factors explain the behaviour of ECOWAS and its success: ECOWAS had a clear legal mandate to threaten the use of force in order to protect democracy in one of its member states; there was consensus that ECOWAS forces could have coped with the relatively small Gambian army; the Gambian president could not rely on friends among his regional peers or some powerful ally from outside Africa; and regional leaders such as Nigeria and Senegal made a credible commitment to the regional intervention. While the intervention was a victory for pro-democratic activist regionalism, the specific West African conditions make a diffusion of the model to other parts of Africa unlikely.